Preserving Biodiversity: The Vital Role of Flora and Fauna in Global Sustainability - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemi, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammed (Darul Yasin Al Sys, 2025)
The ecological balance of the planet, human well-being, and the vitality of natural systems are inextricably linked to the diversity of flora and fauna—biological resources that sustain life through myriad ecosystem services. Flora, comprising the world’s plant life, is fundamental to oxygen production, carbon sequestration, and photosynthetic energy transfer, forming the base of nearly all food webs. Fauna, encompassing animal life, plays critical roles in pollination, seed dispersal, pest regulation, and nutrient cycling. The vast biodiversity encapsulated in global flora and fauna represents the outcome of millions of years of evolution and adaptation. However, unprecedented anthropogenic pressures—including deforestation, habitat destruction, pollution, climate change, overexploitation, and biological invasions—have precipitated significant biodiversity loss in the twenty-first century. This decline jeopardizes not only ecological stability but also the essential services that underpin human health, agriculture, and economic development. In response, disciplines such as environmental science, conservation biology, and sustainable development have mobilized to advocate for the protection of biodiversity through international frameworks like the Convention on Biological Diversity (CBD), targeted species and habitat conservation programs, and enhanced biodiversity monitoring systems. This paper underscores both the intrinsic and utilitarian value of biodiversity, highlighting the urgent need for coordinated global action. Ensuring the persistence of biological diversity demands reinforced environmental governance, expanded protected area networks, ecological restoration, and the integration of sustainability principles into development agendas. The survival of flora and fauna is not only an environmental imperative but a foundation for human resilience and planetary sustainability.